A message passing approach for resource allocation in cellular OFDMA communications - Abrardo, Andrea; Belleschi, Marco; Fodor, Gabor; Moretti, Marco (2012 IEEE Global Communications Conference, 2012)
This paper proposes a distributed and low-complexity resource allocation scheme for cellular OFDMA networks. In particular, we consider ReMP, a reweighted message passing algorithm that perturbs the standard max-sum algorithm by suitably reweighting messages. In a single-cell scenario, such a scheme allows to achieve convergence to a fixed and provably optimum point without employing any central controller. The ReMP algorithm is then adapted to a multi-cell environment. To this aim, we devise X-ReMP, a ReMP-based algorithm that combines cross-cell signaling and the regular ReMP routine that still runs within each cell. The cross-signaling among cells aids ReMP to deal with the inter-cell multiple-access interference, so that X-ReMP allows convergence to a good working point in terms of system throughput even in presence of strong inter-cell interference.